2012
DOI: 10.1126/scitranslmed.3002925
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Vectors Derived from a Large Collection of Simian Adenoviruses Induce Potent Cellular Immunity Across Multiple Species

Abstract: Replication defective Adenovirus vectors based on the human serotype 5 (Ad5) have been shown to induce protective immune responses against diverse pathogens and cancer in animal models and to elicit robust and sustained cellular immunity in humans. However, most humans have anti-Ad5 neutralising antibodies that can impair the immunological potency of such vaccines. Here we show that most other human Adenoviruses from rare serotypes are far less potent as vaccine vectors than Ad5 in mice and non-human primates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
313
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(324 citation statements)
references
References 47 publications
11
313
0
Order By: Relevance
“…rAd serotype 5 (rAd5) is the most potent vector in preclinical and clinical studies but has high seroprevalence in human populations due to natural infection (8,9), which may limit optimal CD8 immunity. This led to the development of alternative rAds based on serotypes with low seroprevalence (2,3,7), but these vary substantially in their potency and protective capacity (7)(8)(9)(10). Of note, a chimpanzee-derived rAd, chAd3, has recently entered accelerated phase I clinical trials for Ebola virus infection, after inducing a high level of protection in a preclinical nonhuman primate model (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…rAd serotype 5 (rAd5) is the most potent vector in preclinical and clinical studies but has high seroprevalence in human populations due to natural infection (8,9), which may limit optimal CD8 immunity. This led to the development of alternative rAds based on serotypes with low seroprevalence (2,3,7), but these vary substantially in their potency and protective capacity (7)(8)(9)(10). Of note, a chimpanzee-derived rAd, chAd3, has recently entered accelerated phase I clinical trials for Ebola virus infection, after inducing a high level of protection in a preclinical nonhuman primate model (11).…”
Section: Introductionmentioning
confidence: 99%
“…While there were clear differences in transcript level across rAds, expression of transcript may not reflect protein expression. Additionally, different adenovirus serotypes can use different receptors to enter target cells (2,3,7,23), which could alter the distribution of Ag across DC subsets and affect CD8 T cell immunity. To assess this directly, mice were vaccinated with rAd5, rAd35, chAd3, and chAd63 encoding EGFP.…”
Section: Introductionmentioning
confidence: 99%
“…Serum IL-10 concentration was measured in BABL/c mice 24 hours after intradermal immunization with 5 x 10 9 viral particles of ChAdV9.ME.TRAP, a vector that belongs to the same serogroup as ChAdV63. 6 IL-10 was quantified using a BD Cytometric Bead Array Mouse Inflammation Kit (BD Biosciences) according to the manufacturer's instructions.…”
Section: Analysis Of Serum Cytokines and Chemokinesmentioning
confidence: 99%
“…3 The field has now turned to rare human adenoviruses (HAdVs 26 and 35) and simian adenovirus ChAdV63 for which seroprevalence in humans is low. 5 However, such vectors may be less potent than HAdV5, 6 though capable of eliciting strong immune responses when included in heterologous primeboost regimens. 5 A potential approach to increasing the immunogenicity of adenovirus vectors is to modulate inhibitory signals, such as interleukin-10 (IL-10), that are induced alongside pro-inflammatory cytokines and chemokines as a compensatory anti-inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented that targeting the most immunogenic epitopes may induce high numbers of Ag-specific CD8 + T cells, but it may also focus the immune response on the selected epitope/Ag, and thus a potential drawback of this approach could be a narrow CD8 + T cell repertoire (24). Adenoviral vectors have been extensively studied as potential vaccine candidates for a number of diseases in which the induction of a robust and long-lasting CD8 + T cell response is considered pivotal (25)(26)(27)(28). We have previously shown that linkage of the vaccine Ag to the MHC class II invariant chain (Ii) can broaden and enhance the Ag-specific CD8 + T response, resulting in improved antiviral protection (29,30).…”
mentioning
confidence: 99%